Ontogeny of Beta 2 Glycoprotein I and Annexin V in Villous Placenta of Normal and Antiphospholipid Syndrome Pregnancies - Donohoe, Siobhán; Kingdom, John C. P.; Mackie, Ian J.; Burrell, Stephen; Quenby, Siobhán; Jauniaux, Eric; Machin, Samuel J. (Thrombosis and Haemostasis, 2000)
β2-glycoprotein I (β2GPI) and annexin V (AV) have been implicated in the pathophysiology of the antiphospholipid syndrome (APS). We investigated their placental expression in normal villous tissues throughout gestation; first trimester n = 10, early second trimester; n = 4, preterm; n = 5) and term; n = 7 and in APS (2 first trimester, 1 preterm and 8 term deliveries). β2GPI and AV were both expressed by the placenta from as early as seven weeks gestation and were colocalised to the syncytiotrophoblast. β2GPI staining was also observed in stromal cells, being present in phagocytic Hofbauer cells and surrounding newly formed fetal vessels in a perivascular pattern, from seven to seventeen weeks gestation. An abnormal morphological distribution of AV was noted in one first trimester APS placenta, and for β2GPI in a further first trimester placenta. When placental proteins were extracted from villous tissue, the concentration of AV/mg protein in term APS placentas (median, interquartile range) (aPS; 8.16, 7.87-9.72 µg/mg) was significantly higher (p <0.005) than normal term levels (normal; 2.47, 2.28-2.54 µg/mg). β2GPI increased with advancing gestation (first trimester; 0.93, 0.64-1.26 µg/mg, term; 3.67, 2.58-4.48 µg/mg) in normal pregnancy. Term APS placentas had a reduced β2GPI content (2.31, 1.87-2.49 µg/mg), p <0.05. The placental role of these proteins remains to be identified.
Keywords: β2-glycoprotein-I; annexin V; placenta; antiphospholipid syndrome (APS)